2014
DOI: 10.3904/kjim.2014.29.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of outdoor air pollution on the incidence of tuberculosis in the Seoul metropolitan area, South Korea

Abstract: Background/AimsAlthough indoor air pollution is a well-known risk factor for tuberculosis (TB), the possible link between outdoor air pollution and TB development has not been examined fully. We assessed the impact of outdoor air pollution on TB development in the Seoul metropolitan area, South Korea.MethodsThe mean concentrations of ambient particulate matter (PM) with an aerodynamic diameter ≤ 10 µm (PM10), O3, CO, NO2, and SO2 levels in Seoul, between January 1, 1997 and December 31, 2006, were determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
88
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 24 publications
8
88
2
Order By: Relevance
“…Specifically, higher concentrations of NO 2 and SO 2 prior to hospital admission were a significant risk factor for hospital admissions. However, no association with CO, O 3 , and PM 10 was found, unlike what has been seen in other studies on the general population [17,2125,50]. This fact could be due to the limited sample size of our group of HIV-infected patients.…”
Section: Discussioncontrasting
confidence: 89%
“…Specifically, higher concentrations of NO 2 and SO 2 prior to hospital admission were a significant risk factor for hospital admissions. However, no association with CO, O 3 , and PM 10 was found, unlike what has been seen in other studies on the general population [17,2125,50]. This fact could be due to the limited sample size of our group of HIV-infected patients.…”
Section: Discussioncontrasting
confidence: 89%
“…In this study, among of all the ambient air pollutants, SO 2 contributed to the lowest concentrations and prolong exposure was significantly associated with PTB. Our findings were consistent with other study in South Korea showing the role of SO 2 in TB infection despite we did not stratified the SO 2 exposure by sex [20]. However, the study in South Korea found only men were susceptible to TB in relation to SO 2 exposure [20].…”
Section: Discussionsupporting
confidence: 92%
“…Stratified by sex, other study in South Korea found PM 10 was not a significant predictor to TB despite the PM 10 concentrations exceeded the national air standards [20].…”
Section: Discussionmentioning
confidence: 83%
“…Outdoor air pollution has been known as one of the risk factors that affect human health directly and/or indirectly [1][2][3][4]. In Korea, it is reported that long-term exposure to ambient air pollution has a reasonable association with tuberculosis, cardiovascular diseases, and preterm delivery [5][6][7]. Thus, periodic monitoring and management of air pollution are required for exposure assessment for effective health management.…”
Section: Introductionmentioning
confidence: 99%